Overview of medication compliance in hypertension patients at haji Adam Malik Hospital Medan 2022 - ziliwu, Vina YS Sigalingging; Saragih, Helinida; Tampubolon, Lindawati F.; Ziliwu, Hendrianus (International Journal on Health and Medical Sciences, 2023)
Hypertension is a disease or disorder in which the blood vessels experience a continuous increase in pressure. Due to an increase in blood pressure which is getting higher, the heart will work hard to pump blood, to avoid this from being bad for the heart and other organs, it is necessary to do treatment, namely by obediently taking the medicine that has been recommended by the doctor. Compliance with taking medication is the behavior of patients who obey all advice and instructions recommended by medical personnel, such as doctors and pharmacists regarding everything that must be done to achieve treatment goals. This type of research uses descriptive research methods. The sampling technique in this study was to use a purposive sampling technique with a total of 30 respondents. The research instrument used was a questionnaire Morisky Medical Adherencem Scale (MMAS-8). The results of this study indicate that of the 30 respondents, 21 respondents (70.0%) took medication in the high category and the least moderate adherence was 9 respondents (30.0%). It is hoped that the results of this study can become material or learning material for nursing students to control blood pressure in hypertensive patients.